Medical Ethics and Health Care System: Medical Ethics in Healthcare System - Zali, Alireza (Bioethics and Health Law Journal (BHL), 2021)
Background and Aim: Daily development of human knowledge, promotion of biomedical technologies, and improvement of physicians' ability in diagnosis and treatment of different types of diseases have always accompanied plenty of discussions and challengeable subjects, especially from the viewpoint of ethical issues. Obtaining deep and accurate recognition of these subjects, the attention of the physicians and the scholars of different fields, especially of ethics has been drawn to medical ethics as a new solution in the comprehensive Healthcare System. Materials and Methods: Available, published, and related articles were located with an Ovid MEDLINE search for "Ethics, Medical," and "Ethics". The Internet was searched for "medical and ethics," "ethics," "science and ethics," and "research and ethics" using the Google search engine (www.google.com). Ethical Considerations: The principles of research ethics have been observed in studies and citing the primary texts and sources. Findings: Despite the great changes in medical technologies, there are still some concerns about the physicians' abilities in decision makings that may directly or indirectly affect the health or life of the people. Therefore, these concerns have led to the appearance of new movements all calling for the patients' rights and the rights of society to participate in medical decision-making. On the other hand, we should notice some other cases that play effective roles in the policy-makings of the comprehensive healthcare system. For instance, the required resources will vary following the changes in technology; the population especially of the elderly is increasing; moreover, the time needed for the new workforces to be entered into the labor market has typically increased. Consequently, a higher number of people are waiting to benefit from the recourses and a lower number of them is involved in producing the recourses. Conclusion: Thus, to work on the important topics like the requirements of human societies, ethical considerations of biotechnology and medical researches, Allocation of limited and immense resources, important ethical criteria of decision makings, representation of fundamental solutions, and medical ethics training is considered as one of the most necessities of comprehensive healthcare system among others. *Corresponding Author: Alireza Zali; Email: dr.zali@sbmu.ac.ir; ORCID: https://orcid.org/0000-0002-2298-2290 Please cite this article as: Zali AR. Medical Ethics and Health Care System. Bioeth Health Law J. 2021; 1: 1-8 (e2). http://doi.org/10.22037/bhl.v1i1.38125